Integrative Therapies for Women with a High Risk Pregnancy During Antepartum Hospitalization. Issue 6 (November 2016) - Schlegel, Merry L.; Whalen, Jeanne L.; Williamsen, Pilar M.
Abstract: Background: High-risk pregnancies that require lengthy hospitalization can cause anxiety and stress for pregnant women. Integrative medicine therapies may be beneficial for this population, but have not been widely studied. Purpose: The purpose of this study was to evaluate potential effects of acupuncture, guided imagery, Healing Touch, massage therapy, and reflexology on pain and anxiety of hospitalized pregnant women. Methods: A retrospective analysis of the effects of integrative medicine therapies was conducted; N = 554 individual therapies were provided to hospitalized women with high-risk pregnancies. They included acupuncture ( n = 83), guided imagery ( n = 71), Healing Touch ( n = 119), massage therapy ( n = 196), and reflexology ( n = 85) over an 18-month period. Pain and anxiety were measured pre- and posttherapy using a scale of 0 to 10, where 0 means no pain or no anxiety and 10 means high pain or high anxiety. Results: Analysis of mean scores of pre- and posttherapies for pain and anxiety found a decrease of pain and anxiety after all of the therapies, ranging from an 84.5% to 61.4% decrease for pain ( p < .0001) and a 91% to 70. 9% decrease for anxiety ( p < .0001). Overall, patients rated their anxiety higher than pain prior to each therapy. Clinical Implications: Hospitalized pregnant women responded favorably to the therapies. There were no adverse reactions reported. Results suggest potential benefits of integrative medicine therapies for this group of inpatients. Anxiety was more prevalent than pain among hospitalized pregnant women who received integrative medicine therapy. Abstract : Being hospitalized due to obstetric or fetal complications can be stressful for pregnant women. Activity restriction or bedrest can be uncomfortable. This innovative program offers integrative therapies to reduce stress and discomfort for pregnant women hospitalized on the antepartum unit. Therapies such as massage, Healing Touch, acupuncture, guided imagery, and reflexology are included. Data on effects of these integrative therapies are presented.